2020
DOI: 10.1101/2020.02.04.933994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A designer FG-Nup that reconstitutes the selective transport barrier of the Nuclear Pore Complex

Abstract: Nuclear Pore Complexes (NPCs) regulate bidirectional transport between the nucleus and the cytoplasm. Intrinsically disordered FG-Nups line the NPC lumen and form a selective barrier, where transport of most proteins is inhibited whereas specific transporter proteins freely pass. The mechanism underlying selective transport through the NPC is still debated. Here, we reconstitute the selective behaviour of the NPC bottom-up by introducing a rationally designed artificial FG-Nup that mimics natural Nups. Using Q… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…From the dynamical point of view, atomic force microscopy measurements (29) showed that FG-Nups fluctuate rapidly inside the nuclear pore. Molecular dynamics (30,31), Langevin dynamics (32)(33)(34)(35)(36), and Brownian dynamics simulations (37)(38)(39)(40)(41) demonstrated the highly dynamic nature of FG-Nups. However, some experimental studies argued that the entropic effect by itself is too weak to account for the mechanical stiffness in the NPC central channel (42,43).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…From the dynamical point of view, atomic force microscopy measurements (29) showed that FG-Nups fluctuate rapidly inside the nuclear pore. Molecular dynamics (30,31), Langevin dynamics (32)(33)(34)(35)(36), and Brownian dynamics simulations (37)(38)(39)(40)(41) demonstrated the highly dynamic nature of FG-Nups. However, some experimental studies argued that the entropic effect by itself is too weak to account for the mechanical stiffness in the NPC central channel (42,43).…”
Section: Introductionmentioning
confidence: 97%
“…To investigate the relation between the entropic barrier effect and the NPC's selective nature, we modeled the free energy by specifically considering the conformational entropy of FG-Nups and the binding interaction between FG-Nups and NTRs. Other groups have previously proposed the models for the NPC's free energy using the molecular theory (51)(52)(53)(54)(55), the density functional theory (56,57), and umbrella sampling of the molecular dynamics simulation trajectories (33,36). Our model is different from prior art in two ways: firstly, we assumed that FG-Nups are homogeneous ideal chains instead of considering their amino acid sequence heterogeneity (33,36,52,54) or intermolecular cohesiveness (56,57).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies provide interesting insights into potential pathways for R-DPRs-mediated NCT defects, the molecular basis for the interaction of longer R-DPRs with different Kapβs and the resulting NCT defects has not yet been identified. In this study, we use coarse-grained (CG) molecular dynamics models [33][34][35][36][37] to investigate the length-dependent interaction of poly-PR (known to be the most toxic DPR [11][12][13]) with different members of the Kapβ family of NTRs with the aim to provide mechanistic insight into the way poly-PR interferes with the transport functionality of Kapβs.…”
Section: Introductionmentioning
confidence: 99%
“…Designer FG-domains, where the composition of the sequence mirrors that of the wild-type proteins (Fragasso et al, 2020) provide an excellent opportunity for constructing sequences amenable to atomic resolution characterization by NMR. Through simplification of the sequence of Tetrahymena thermophila MacNup98A (TtMacNup98A), Ng and Görlich obtained a perfectly repetitive sequence that could entirely recapitulate the permselectivity properties of the full-length protein and of nuclear pores (Ng and Görlich, 2021) (unpublished).…”
Section: Native Conformation Of Fg-domainsmentioning
confidence: 99%